Mapping the evolution and future prediction of berthing ship CO2 emissions in China - Zhu, Enyan; Ye, Aohan; Chen, Lisu; Zhang, Taiguo; Yao, Jian; Liu, Tao (Frontiers in Marine Science, 2025)
IntroductionRapid expansion of the shipping industry is not only boosting trade and economic growth, but also leading to increased CO2 emissions, which presents substantial challenges to climate change mitigation. Therefore, it is of great significant to simulate the berthing ship emission reduction potential under the context of global change.MethodsBased on the spatial-temporal evolution as well as the driving factors of the port ship CO2 emissions, this study predicted the future port ship CO2 emission patterns in China.ResultsResults indicated an obvious divergence in CO2 spatial-temporal distributions, and the high-emission areas had shifted from the northern to the southern ports. The volume of waterway transportation, road transportation, Gross Domestic Product (GDP) and the proportion of the secondary industry were the primary drivers of the port ship CO2 emissions, though the influence degree of each factor varied across different ports.DiscussionFinally, scenario-based forecasts suggested that advancing ship energy efficiency technologies and formulate robust emission reduction policies were urgently needed to mitigate the environmental impact of port activities.